FEMINIST LITERARY THEORY : A READER - MARY EAGLETON (U S A JOHN WILEY & SONS, 2011)
Feminist Literary Theory: A Reader constitutes one of the classic texts of second-into-third-wave feminist literary studies. Both a history and a survey of the varied positions within feminist literary theory, the Reader includes extracts from all the major critics, critical approaches, and theoretical positions in contemporary feminist literary studies.
Keywords: Feminist Literary Criticism -- Feminism and Literature -- Women and Literature